Introducing English syntax a basic guide for students of English - Fenn, Peter; Schwab, Gotz (Routledge, Taylor & Francis Group, 2018)
Introducing English Syntax provides a basic introduction to syntax for students studying English as a foreign language at university. Examining English phrase and sentence structure from a descriptive point of view, this book develops the reader's understanding of the characteristic features of English sentence construction and provides the necessary theoretical apparatus for engaging with the language. Key features include A unique framework combining theoretical and practical approaches to provide an insight into the intricacies of English syntax, An accessible and clear style which guides the learner through analysis, application and practical construction of sentences, A range of exercises at the end of each chapter and a brand new e-resource housing answers and commentaries to these exercises. This book requires no previous knowledge of linguistics and is essential reading for students and teachers of applied linguistics and EFL/ESL, as well as those who seek a basic grounding in English sentence structure.